Strategi Untuk Mengendalikan Inflasi Menurut Perspektif Ekonomi Islam - Luk Lu’us Syarifah; Husnul Khotimah; Yusnia Yusnia (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Inflation is an economic issue that is often discussed in Indonesia. Where inflation is an economic phenomenon that involves an increase in goods and services in the world economy. However, in the context of Islamic economics, inflation is not just a difference in prices, but leads to ethical and social differences that violate sharia principles. Indonesia has made various efforts to control inflation, including controlling supply and demand, stabilizing prices of daily necessities, and regulating monetary and fiscal policies. This research aims to find out strategies for controlling inflation according to Islam. This research uses a qualitative approach using systematic literature review (SLR) techniques. to control inflation according to Islamic economics. This fiscal policy includes state spending for the public interest, taxes and loans to stabilize the national economy and public welfare, or is controlled by sharia money, namely by avoiding the use of instruments based on usury, gharar, maisyir and zhulum. Islamic economics as an economic system has its own methods and strategies for controlling inflation which are very different from other economic systems. Islamic economics accepts monetary and fiscal policy as part of efforts to control inflation. However, to achieve standards of socio-economic justice, efforts need to be made to maintain price stability through strategies of moral improvement, equal distribution of income and wealth, and the elimination of usury.